Studying the Effect of Using Ultrasound Vibration on the Reproduction of Detail and Surface Hardness of Dental Stone Models - Ali M. Aljafery; Mohammed Alkafagy; Zena J. Wally; Athraa Mohammed Dheyaa; Raja'a M. Almusawi; Julfikar Haider (Nano Biomedicine and Engineering, 2022)
BackgroundThe accuracy of surface production details in the dental models determines the success of the dental prosthesis in clinical application.AimThis in vitro study aims to compare between dental stone models produced using two types of techniques for pouring the addition silicone impression.MethodThe control group was poured using the conventional vibration technique at a vibration frequency of 3000 cycles/min and the experimental group was poured by an ultrasound vibration technique at a frequency of 28 kHz in order to assess the difference in pouring techniques in terms of reproduction of details and surface hardness. A stainless steel die, prepared based on the ISO 6873, was employed to fabricate samples for evaluating the surface details. Fisher's exact test scoring scale was employed to qualititatively assess the reproduced surface details. Vickers hardness was measured to evaluate the surface hardness of cylindrical stone samples poured by the two different techniques.ResultsThe results indicated that the reproduction of details of the stone samples poured by the ultrasound vibration technique were not significantly different (P > 0.05) in comparison with that poured by the conventional vibration technique. However, the surface hardness was significantly enhanced (P = 0.04) by the ultrasound vibration pouring technique.ConclusionAlthough the application of ultrasound vibration during dental cast fabrication did not provide any significant clinical advantages in terms of surface reproducibility, it could significantly improve the surface hardness compared with the traditional vibration technique.